2017
DOI: 10.1161/hypertensionaha.117.09048
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Hypotension and Risk of Incident Dementia

Abstract: Abstract-Several studies indicate a potential link between orthostatic hypotension (OH) and incident dementia but without substantial evidence to date. Our objective is to study the association between OH and dementia in a cohort of elderly individuals. To do so, baseline lying and standing blood pressure measurements were taken from 7425 subjects in the Three-City study. These subjects were then followed-up for 12 years. Cox proportional hazard models, adjusted for potential confounders, were used to estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 34 publications
3
32
0
1
Order By: Relevance
“…In line with previous studies performed in the general population, prevalence of OH was high and increased across the spectrum of SCD, to MCI, and dementia [7, 8]. In most community-based cohort studies [9, 11], however, the prevalence of different types of dementia was too low to assess whether patients with OH are more likely to have any particular type of dementia. We observed that the prevalence of OH was highest in patients with DLB and VaD, which has been previously reported [7, 25], and is to be expected as autonomic dysfunction is a well-known feature in α -synucleinopathies like DLB [26], while OH and VaD are both features of systemic vascular pathology [4].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In line with previous studies performed in the general population, prevalence of OH was high and increased across the spectrum of SCD, to MCI, and dementia [7, 8]. In most community-based cohort studies [9, 11], however, the prevalence of different types of dementia was too low to assess whether patients with OH are more likely to have any particular type of dementia. We observed that the prevalence of OH was highest in patients with DLB and VaD, which has been previously reported [7, 25], and is to be expected as autonomic dysfunction is a well-known feature in α -synucleinopathies like DLB [26], while OH and VaD are both features of systemic vascular pathology [4].…”
Section: Discussionsupporting
confidence: 83%
“…OH can be categorized into early OH occurring only at 1 minute after standing and delayed and/or prolonged OH occurring at (1 and) 3 minutes after standing [6]. In the general population, OH has proven to be more prevalent in older adults with mild cognitive impairment (MCI) and dementia [7, 8], and has been associated with incident MCI and incident dementia [9–12]. However, less is known about the link between OH, MCI, and dementia in a clinical setting (i.e., patients visiting a memory clinic).…”
Section: Introductionmentioning
confidence: 99%
“…At the population level, OH does not appear to be linked to a particular dementia type. In line with dementia prevalence in the general population, Alzheimer’s disease, vascular dementia, and mixed-type dementia were the most common in the population-based studies we reviewed, accounting for over 80% of incident dementia; DLB/PD dementia represented less than 10% 41,42. The Rotterdam study reported similar hazard ratios for both the Alzheimer’s disease and vascular dementia subgroups, but the incidence of other dementias was too low to assess risk 41.…”
Section: Oh and Incident Cognitive Declinementioning
confidence: 79%
“…Further, a continuous scale of orthostatic dysregulation – quantified as SBP variability – was associated with an increased risk of dementia; a finding that persisted even in a subgroup that excluded individuals with classic OH. In the French Three-City Study, 7,425 community-living individuals older than 65 years of age were tracked over a mean follow-up period of 7.5 years, during which time 760 cases of dementia were diagnosed 42. OH was associated with a ~20% increased risk of incident dementia; however, when a more stringent threshold for OH was used (ie, SBP drop>30 mmHg or DBP drop>15 mmHg), the risk of dementia was even greater (~57%).…”
Section: Oh and Incident Cognitive Declinementioning
confidence: 99%
“…В R. Peters и соавт. [37] провели также метаанализ результатов пяти исследований: HYVET [37], Malmö Preventive Project [34] и SNAC [35], Three-City Study [36] и Роттердамского исследования старения [30] и установили, что нали-чие ОГ ассоциировано с увеличением риска развития деменции на 21% (ОР 1,21; 95% ДИ 1,09-1,35).…”
unclassified